Islam and Local Culturation in the Cukur Gembel Tradition of Dieng, Wonosobo - Munandar, Siswoyo Aris; Fahrurrozi, Muhammad (Indigenous Southeast Asian and Ethnic Studies, 2025)
Indonesia is a pluralistic nation with rich cultural diversity, one example being the Ruwatan Cukur Gimbal (Dreadlocks Shaving Ritual) in Dieng Village, Wonosobo Regency. Children with dreadlocks are regarded as special, and their hair is not cut until they or their parents request it, often after fulfilling unusual wishes such as a basket of eggs, a mouse, or traditional food. This study examines the tradition through cultural and Islamic perspectives using a case study approach, with data gathered from interviews, observations, and document analysis. Findings show that the ritual has deep historical roots linked to Kyai Kolo Dete and Nyai Roro Kidul. Beyond being a cultural event, it incorporates religious aspects such as Qur’anic recitations, prayers, and the Javanese hymn Kidung Rumekso Ing Wengi, attributed to Sunan Kalijaga. The ceremony reflects tolerance, spirituality, and communal harmony, while in an Islamic framework it promotes togetherness, respect for parents, and the significance of prayer. As the tradition continues to evolve, preserving it in harmony with Islamic values is crucial. Thus, the Cukur Gimbal ritual serves not only as a marker of cultural identity but also as a medium for reinforcing Islamic values within the community.